Sistem Pendukung Keputusan Pemberian Reward Bulanan Teknisi Pasang Baru Indihome Menggunakan Metode Weighted Product Studi Kasus PT Telkom Akses Kepanjen - Saputro, Firman Adi; Isyriyah, Laila (J-INTECH (Journal of Information and Technology), 2021)
PT.Telkom Akses Kepanjen is a state-owned company PT Telkom Indonesia which engaged in information technology services and communications with a product called Indonesia Digital Home (INDIHOME). Installation, handling, maintenance, and network migration activities are the responsibility of PT. Telkom Access as a company of PT Telkom Indonesia which trusted to manage access to learning. In order to increase company income PT Telkom Access through the new installation sector (PSB) requires good management of human resources by management so that technical performance can be carried out according to the vision and management of the company. One of them is by providing a reward as a form of appreciation for technical performance as well as for improving technician performance. But the ongoing reward giving is only a par with the amount of acquisition of new pairs or provisioning starts (PS) so that the performance indicator (KPI) is not included in the assessment parameters. The system of support for the decision to give new pairs of technical returns by using the weighted product method is very helpful for management for the process of giving monthly returns to new pairs of technicalities by using several parameters including PI to PS, FFG, TTI, data validation, attendance, attendance and photo briefing, accuracy of work attendance and work permit. The results of the application of reward system by using the weighted product method on some of these parameters can produce more competitive and varied a reward values ​​between technicalities and greatly assist the management of PT Telkom Akses Kepanjen in determining the rewards of paper as a new evaluation material for technical performance.